2009
DOI: 10.1186/1755-8794-2-27
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of HIV-1 virus-host protein interactions using virus and host sequence motifs

Abstract: Background: Host protein-protein interaction networks are altered by invading virus proteins, which create new interactions, and modify or destroy others. The resulting network topology favors excessive amounts of virus production in a stressed host cell network. Short linear peptide motifs common to both virus and host provide the basis for host network modification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
100
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(100 citation statements)
references
References 44 publications
0
100
0
Order By: Relevance
“…Analysis of PPI structural data revealed that virus-host interacting interfaces bury smaller surface areas (ϳ950 Å 2 ) than internal cellular interactions (ϳ1,780 Å 2 ) (40). Of course, the weaker virushost PPIs must compete with the stronger host-host PPIs, and this is apparently achieved with sheer numbers, since the high copy number of viral proteins in the infected cell can push the equilibrium toward the virus-host interaction (53). The origin of the weaker virus-host interactions is probably a result of viral protein evolution toward supporting flexible interactions with various partners.…”
Section: Molecular Basis Underlying Flexible Exploitation Of Cellularmentioning
confidence: 99%
See 2 more Smart Citations
“…Analysis of PPI structural data revealed that virus-host interacting interfaces bury smaller surface areas (ϳ950 Å 2 ) than internal cellular interactions (ϳ1,780 Å 2 ) (40). Of course, the weaker virushost PPIs must compete with the stronger host-host PPIs, and this is apparently achieved with sheer numbers, since the high copy number of viral proteins in the infected cell can push the equilibrium toward the virus-host interaction (53). The origin of the weaker virus-host interactions is probably a result of viral protein evolution toward supporting flexible interactions with various partners.…”
Section: Molecular Basis Underlying Flexible Exploitation Of Cellularmentioning
confidence: 99%
“…The late assembly domains (PTAP and YPXL of HIV-1 Gag-p6) mimic comparable cellular interfaces in the exploitation of the cellular ESCRT pathway of membrane fission (e.g., Gag PTAP mimics cellular HRS protein in binding the UEV domain of TSG101) (37,38). Given their functional essentiality, these short motifs are highly conserved (11,52,53), function independently of their location within the targeting protein, and can be functionally exchanged with comparable motifs from other proteins (39,55).…”
Section: Molecular Basis Underlying Flexible Exploitation Of Cellularmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal cell functioning of viral hosts is altered by invading virus proteins to the benefit of the virus (Evans et al, 2009). Viral proteins are known to compete with the host proteins thus disrupting the normal host protein-protein interaction network (Sodhi et al, 2004;Tournier & Quesnel-Hellmann, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Normal cell functioning of host is altered by invading viral proteins to the benefit of the virus [11]. There have been constant efforts to understand these interactions between viral and cellular gene products which together determine the host's susceptibility to infection and disease progression in HIV-1 infection [12].…”
Section: Introductionmentioning
confidence: 99%